The CLAVATA receptor FASCIATED EAR2 responds to distinct CLE peptides by signaling through two downstream effectors - Byoung Il Je; Fang Xu; Qingyu Wu; Lei Liu; Robert Meeley; Joseph P Gallagher; Leo Corcilius; Richard J Payne; Madelaine E Bartlett; David Jackson (eLife, 2018)
Meristems contain groups of indeterminate stem cells, which are maintained by a feedback loop between CLAVATA (CLV) and WUSCHEL (WUS) signaling. CLV signaling involves the secretion of the CLV3 peptide and its perception by a number of Leucine-Rich-Repeat (LRR) receptors, including the receptor-like kinase CLV1 and the receptor-like protein CLV2 coupled with the CORYNE (CRN) pseudokinase. CLV2, and its maize ortholog FASCIATED EAR2 (FEA2) appear to function in signaling by CLV3 and several related CLV3/EMBRYO-SURROUNDING REGION (CLE) peptide ligands. Nevertheless, how signaling specificity is achieved remains unknown. Here we show that FEA2 transmits signaling from two distinct CLE peptides, the maize CLV3 ortholog ZmCLE7 and ZmFON2-LIKE CLE PROTEIN1 (ZmFCP1) through two different candidate downstream effectors, the alpha subunit of the maize heterotrimeric G protein COMPACT PLANT2 (CT2), and ZmCRN. Our data provide a novel framework to understand how diverse signaling peptides can activate different downstream pathways through common receptor proteins.